Secondary Germline Finding in Liquid Biopsy of a Deceased Patient; Case Report and Review of the Literature - Veyseh, Maedah; Ricker, Charite; Espenschied, Carin; Raymond, Victoria; D’Souza, Anishka; Barzi, Afsaneh (Frontiers in Oncology, 2018)
Liquid biopsies are increasingly used in the care of patients with advanced cancers. These tests are used to find mutations and other genomic alterations, quantify these findings over time, and guide treatment. It is not unexpected that germline mutations contributing to the development of cancer can be identified in cell-free DNA. Consequently, increased use of liquid biopsies has resulted in subsequent rise of secondary identification of germline mutations. Clinicians need to be aware of this potential use of liquid biopsies and the need to evaluate the patient and family members for confirmation. Our case documents a deceased patient’s liquid biopsy result that was confirmed as a germline mutation through a methodical work-up of the patient’s family members. Here, we present the case and provide a brief review of pertinent literature.